Visual search strategy in judo fighters during the execution of the first grip - Piras, A.; Pierantozzi, E.; Squatrito, S. (International Journal of Sports Science and Coaching, 2014)
Visual search behaviour is believed to be very relevant for athlete performance, especially for sports requiring refined visuo-motor coordination skills. Modern coaches believe that optimal visuo-motor strategy may be part of advanced training programs. Gaze behaviour of expert and novice judo fighters was investigated while they were doing a real sport-specific task. The athletes were tested while they performed a first grip either in an attack or defence condition. The results showed that expert judo fighters use a search strategy involving fewer fixations of longer duration than their novice counterparts. Experts spent a greater percentage of their time fixating on lapel and face with respect to other areas of the scene. On the contrary, the most frequently fixed cue for novice group was the sleeve area. It can be concluded that experts orient their gaze in the middle of the scene, both in attack and in defence, in order to gather more information at once, perhaps using parafoveal vision